Earthquake Engineering - Sezen, Halil (IntechOpen, 2012)
Recent major earthquakes around the world have shown the vulnerability of infrastructure and the need for research to better understand the nature of seismic events and their effects on structures. As a result, earthquake engineering research has been expanding as more and more data become available from a large array of seismic instruments, large scale experiments and numerical simulations. The first part of this book presents results from some of the current seismic research work including three-dimensional wave propagation in different soil media, seismic loss assessment, probabilistic hazard analysis, geotechnical problems including soil-structure interaction. The second part of the book focuses on the seismic behavior of structures including historical and monumental structures, bridge embankments, and different types of bridges and bearings.